Protective effect of bioactive iridium nanozymes on high altitude-related hypoxia-induced kidney injury in mice - Wang, Yujing; Shi, Meijun; Chu, Zongtang; Yan, Xinlin; You, Guoxing; Chen, Gan; Zhou, Hong (Frontiers in Pharmacology, 2023)
High altitude-related hypoxia-induced organ damage significantly impacts people who are exposed to acute high-altitude environment. At present, kidney injury still lacks effective treatment strategies. Iridium nanozymes (Ir-NPs) are a nanomaterial with various enzymatic activities and are expected to be used in kidney injury treatment. In this study, we simulated a high-altitude environment (6000 m) to induce a kidney injury model, and explored the therapeutic effect of Ir-NPs in mice with kidney injury in this environment. Changes in the microbial community and metabolites were analyzed to explore the possible mechanism underlying the improvement of kidney injury during acute altitude hypoxia in mice treated with Ir-NPs. It was discovered that plasma lactate dehydrogenase and urea nitrogen levels were considerably increased in mice exposed to acute altitude hypoxia compared to mice in a normal oxygen environment. Furthermore, there was a substantial increase in IL-6 expression levels in hypoxic mice; contrastingly, Ir-NPs decreased IL-6 expression levels, reduced the levels of succinic acid and indoxyl sulfate in the plasma and kidney pathological changes caused by acute altitude hypoxia. Microbiome analysis showed that bacteria, such as Lachnospiraceae_UCG_006 predominated in mice treated with Ir-NPs. Correlation analysis of the physiological, biochemical, metabolic, and microbiome-related parameters showed that Ir-NPs could reduce the inflammatory response and protect kidney function under acute altitude hypoxia, which may be related to intestinal flora distribution regulation and plasma metabolism in mice. Therefore, this study provides a novel therapeutic strategy for hypoxia-related kidney injury, which could be applied to other hypoxia-related diseases.